Phase I clinical and pharmacokinetic study of pemetrexed and carboplatin in patients with malignant pleural mesothelioma - Hughes, Andy; Calvert, Paula; Azzabi, Ashraf; Plummer, Ruth; Johnson, Rob; Rusthoven, Jim; Griffin, Melanie; Fishwick, Kevin; Boddy, Alan V; Verrill, Mark; Calvert, Hilary (Journal of clinical oncology, 2002)
To determine the maximum tolerated dose (MTD) of pemetrexed and carboplatin given in combination, to derive a recommended dose for phase II studies, and to explore its efficacy. We assessed toxicities and explored the activity of the drug combination exclusively in patients with malignant pleural mesothelioma (MPM). The pharmacokinetics of both agents was investigated. Twenty-seven patients (23 male, four female) with MPM were treated on five escalating dose levels. Doses ranged from pemetrexed 400 mg/m(2) (as a 10-minute intravenous infusion), followed by carboplatin area under the plasma concentration-time curve (AUC) 4 mg/mL.min (as a 30-minute intravenous infusion) to pemetrexed 500 mg/m(2), carboplatin AUC 6 mg/mL.min. All patients had a World Health Organization performance status of 1. A total of 163 courses of treatment were administered (median, six; range, one to 10). The main toxicity was hematologic, particularly neutropenia, although this was characteristically short-lived and caused few clinical problems. The MTD was pemetrexed 500 mg/m(2), carboplatin AUC 6, because three of the five patients treated at this dose level experienced a dose-limiting toxicity. Eight partial responses (in 25 assessable patients) were observed for a response rate of 32%. Seventy percent of patients noticed an improvement in symptoms, usually (84%) after only two courses. Median time to progression was 305 days, and median survival time was 451 days. The MTD was pemetrexed 500 mg/m(2) and carboplatin AUC 6 mg/mL.min. The recommended phase II dose of the combination is pemetrexed 500 mg/m(2) and carboplatin AUC 5 mg/mL.min. The combination is both active and well tolerated in MPM and deserves further exploration.